2007
DOI: 10.3354/dao074243
|View full text |Cite
|
Sign up to set email alerts
|

Synechocystis MCCB 114 and 115 as putative probionts for Penaeus monodon post-larvae

Abstract: MATERIALS AND METHODS Cyanobacterial cultures.Water samples (n = 9) were collected from surface waters of the sea surrounding Vypeen Island (09°58' N, 76°17' E) using a Niskin ABSTRACT: Synechocystis MCCB 114 and 115 were segregated as putative probionts for shrimp larvae from a collection of 54 cyanobacterial cultures enriched from seawater. On feeding Penaeus monodon post-larvae with the cyanobacteria, the generic diversity of the intestinal bacterial flora could be enhanced with substantial reduction or tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In other work, Penaeus monodon postlarvae specimens fed supplemented diet with 10 9 cfu g -1 diet of two strains of Synechocystis sp. (C51 and C54) separately for twenty days showed significantly better survival after infection with Vibrio harveyi MCCB 111 than those fed without probiotics [37]. Also in postlarvae specimens, dietary administration of Bacillus sp.…”
Section: Probiotics Against Bacteria In Shellfishmentioning
confidence: 89%
“…In other work, Penaeus monodon postlarvae specimens fed supplemented diet with 10 9 cfu g -1 diet of two strains of Synechocystis sp. (C51 and C54) separately for twenty days showed significantly better survival after infection with Vibrio harveyi MCCB 111 than those fed without probiotics [37]. Also in postlarvae specimens, dietary administration of Bacillus sp.…”
Section: Probiotics Against Bacteria In Shellfishmentioning
confidence: 89%
“…Numerous studies have shown enhanced growth, survival and health status of marine larvae cultured with microalgae (e.g., Isochrysis galbana, Tetraselmis suecica, Phaedactylum tricornutum, Dunaliella salina or Dunaliella tertiolecta) (e.g., Nass et al 1992;Reitan et al 1997;Cahu et al 1998;Suppamattaya et al 2005). Preetha et al (2007) established marine cyanobacterium Synechocystis MCCB 114 and 115 as putative probionts for shrimp P. monodon. Different hypotheses have been suggested to explain the beneficial effects of algae to the larvae, such as (1) direct supply of nutrients (Reitan et al 1997); (2) stimulation of the digestive abilities of larvae (Cahu et al 1998); (3) influence on the bacterial population of the rearing water and thus contributing to the establishment of an early gut microbial flora in the larvae (Bergh et al 1994;Skjermo and Vadstein 1999).…”
Section: Microalgaementioning
confidence: 99%
“…At present, people mainly screen out marine probiotics from seawater, sediment, fish mucus, aquatic organism digestive tract, etc. [ 6 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%